Ultrahigh-throughput single-pixel complex-field microscopy with frequency-comb acousto-optic coherent encoding (FACE) - Daixuan Wu; Yuecheng Shen; Zhongzheng Zhu; Tijian Li; Jiawei Luo; Zhengyang Wang; Jiaming Liang; Zhiling Zhang; Yunhua Yao; Dalong Qi; Lianzhong Deng; Zhenrong Sun; et al. (Light: Science & Applications)
Abstract Single-pixel imaging (SPI) is a promising technology for optical imaging beyond the visible spectrum, where commercial cameras are expensive or unavailable. However, limitations such as slow pattern projection rates and time-consuming reconstruction algorithms hinder its throughput for real-time imaging. Consequently, conventional SPI is inadequate for high-speed, high-resolution tasks. To address these challenges, we developed an ultrahigh-throughput single-pixel complex-field microscopy (SPCM) system utilizing frequency-comb acousto-optic coherent encoding (FACE). This system enables real-time complex-field monitoring in the non-visible domain. Operating at 1030 nm, our system achieves a record-high space-bandwidth-time product (SBP-T) of 1.3 × 107, surpassing previous SPCM (~104), SPI (~105), and even certain types of commercial near-infrared cameras (~106). It supports real-time streaming at 1000 Hz with a frame size of 80 × 81 pixels and a lateral resolution of 3.76 μm across an approximately 300 μm field of view. We validated the system by imaging dynamic transparent scenes, including microfluidics, live microorganisms, chemical reactions, as well as imaging through scattering media. This advancement offers a superior solution for high-speed, high-resolution complex-field imaging beyond the visible spectrum, significantly enhancing SPI performance across various applications.